=−37−x−23+15
=−x−(37+23)+15
=−x−60+15
=−x−(60−15)
=>−x−45
=−37−x−23+15
=−x−(37+23)+15
=−x−60+15
=−x−(60−15)
=>−x−45
Rút gọn biểu thức:
a) (-37) – (x + 23) + 15 =
b) 176 – (176 - x + 42) =
c) 1270 – (1270 – 2x) + 31 =
d) 2x + (-141) – (231 – 461) =
Rút gọn biểu thức: A = (x - 15) - [(57 + x) - (23 - x)]
Rút gọn các biểu thức sau:
a) M=(71+x)-(-24+x)+(-35-x)
b) N=x-34-[(15+x)-(23-x)]
Rút gọn các biểu thức sau:
a. A = (71 + x) − ( − 24 − x) + ( − 35 − x).
b. B = x − 34 − [(15 + x) − (23 − x)].
c. C = ( − 15 + | x | ) + (25 − | − x | ).
Xin các tiên sinh hộ giáo !
Rút gọn các biểu thức sau:
a/ (71+x) - [(-24) - x] + [(-35) - x ]
b/ x - 34 - [(15 + x) - (23 - x)]
c/ 26 - [(-x) + 126 - 13) + [(-113) + x]
Rút gọn biểu thức:
a) x + 31 + (-12) + 52; b) (-35) - (x + 23) + 61;
c) 127- (127 - x) + 23; d) 107 - (107 + x - 23)
rút gọn biểu thức :
[-15 + (-x )] +[ 25 - (-x)]
rút gọn biểu thức:(-15)-(x+13)+11
Rút gọn biểu thức sau: E=/21-/x-15// với x<15.